The effectiveness of three phosphorus sources for pasture fertilization in a cerrado soil - Couto, Walter; Leite, Gilberto; Sanzonowicz, Cláudio (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment with three phosphorus sources (triple superphosphate (TSP), thermal phosphate (TP) and phosphate rock (PR)) and two levels of lime was conducted in an acid oxisol of low fertility (clayey oxidic typic acrustox) to determine the amount of P required for establishment of a legume-based pasture, the relative efficiency of three sources and, the response to three rates of annual refertilization. The pasture was an association of Andropogon gayanus Kunth, var. bisquamulatus (Hoechst Hack) cv. Planaltina and Stylosanthes capitata (Vog) CIAT 1078. Best results were obtained with TP, specially during first and second year. This effect occurred at both 0 and 1650 kg ha-1 of Mg enriched lime (Calcium carbonate equivalent = 602). Forage yield obtained with 26 P kg ha-1 as TSP and PR at double rate (52 P kg/ha) increased with time, being similar to that obtained with TP (26 P kg/ha) by the fourth year. Annual refertilization at 13 and 26 P kg/ha improved yield during second and third years but yield increase due to annual refertilization decreased on time. Pasture response (o annual refertilization depended on P source but was not affected by initial P rate. Despite the relatively high amount of P and other nutrients being applied, pasture establishment was very slow and forage yield considerably low, reaching 3.8 ton ha-1 year-1 with best treatments.